An experience of abdominal repair of high genitourinary fistulae (Nepal Journal of Obstetrics and Gynaecology, 2018)
Aims: We aim to present our experience of repair of genitourinary fistulae by abdominal approach with special emphases on repairs of high fistula.Methods: This study includes all the patients from January 2016 to December 2017 who underwent abdominal repair of VVF. The patient who had vaginal repair of VVF were excluded.Results: Forty cases were included in the study. Mean age was ( 20-50) 34.8 years with parity ranging from 2-8, Out of 40 cases 13( 32.5 %) were vesico cervical, 5(12.5%) were vesico uterine and 22 (55.00%) were vault fistula. So these all were high fistula involving uterus, cervix and vault, resulting after caesarean section, caesarean hysterectomy and Gynecological hysterectomy. All had abdominal repair which was successful in 39 cases giving success rate of (97.5%).Conclusions: An abdominal approach seems to give superior results especially for high fistulae.